Characterizing downwind drift deposition of aerially applied glyphosate using RbCl as tracer - Huang, Yanbo; Ouellet-Plamondon, Claudiane M.; Thomson, Steven J.; Reddy, Krishna N. (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Rubidium chloride (RbCl) was used as a tracer tank-mixed with active ingredients to profile downwind deposition of aerially applied crop protection and production materials to characterize off-target drift, which helps improve spray efficiency and reduce environmental contamination. Mylar sheets were placed on a holder in the field at each sampling station to collect sprayed solution. RbCl tracer was used to assess downwind drift of nozzles mounted on the booms installed and controlled on both sides of an agricultural airplane. The experiment was conducted on a field covered by Bermuda grass (Cynodon dactylon). During the experiment, the airplane was planned to fly three passes with three replications at each of three different altitudes, 3.7 m, 4.9 m, and 6.1 m for total of 27 flight runs. The results indicated that sampling station location had a significant effect on RbCl concentration. However, application release altitude was not significant to the change of RbCl. Another practical application in the same aerial application system was used to assess crop injury from the off-target drift of aerially applied glyphosate. RbCl concentrations measured from Mylar sheets were correlated with visual injury, plant height, shoot dry weight, leaf chlorophyll content, and shikimate, which were measured from the leaves and plant samples collected. Overall, RbCl is an effective tracer for monitoring spray applications from agricultural aircraft and unmanned aerial vehicles to intensify agriculture output and minimize environmental impact. Keywords: Rubidium chloride (RbCl), precision agriculture, spray efficiency, off-target drift, aerial application, herbicide, crop injury, environmental pollution DOI: 10.3965/j.ijabe.20171003.3351 Citation: Huang Y B, Ouellet-Plamondon C M, Thomson S J, Reddy K N. Characterizing downwind drift deposition of aerially applied glyphosate using RbCl as tracer. Int J Agric & Biol Eng, 2017; 10(3): 31–36.